Functional characterization of a putative lipopolysaccharide-induced TNF-alpha factor (LITAF) from blood clam Tegillarca granosa in innate immunity. Issue 97 (February 2020) - Liu, Guosheng; Li, Zengpeng; Yang, Minghan; Lin, Linjun; Liu, Jinqiang; Chen, Mingliang
Abstract: Lipopolysaccharide-induced TNF-alpha factor (LITAF), as a transcription factor, activates the transcription of TNF and other cytokines in inflammatory response upon lipopolysaccharide (LPS) stimulation. In the present study, we cloned and identified the full-length cDNA of LITAF homolog from blood clam Tegillarca granosa for the first time. The full-length cDNA of Tg LITAF was 1801 bp encoding a polypeptide of 147 amino acids with an estimated molecular mass of 16.13 kDa. Tg LITAF contained a zf-LITAF-like zinc ribbon domain at the C-terminal of the protein and the Tg LITAF domain showed 48–74% amino acid sequence identity with other known LITAFs from other species. Subcellular localization study showed that Tg LITAF was mainly expressed in the nucleus. qRT-PCR analysis showed that the Tg LITAF transcription expressed constitutively in all the examined tissues with the highest expression level in the gills. After LPS or V. alginolyticus treatment, expression of Tg LITAF in hemocytes was both up-regulated significantly at 3–6 h. Furthermore, in vitro study indicated that overexpression of Tg LITAF in HeLa cells resulted in the activation of TNFα, p53, and influenced the expression levels of apoptotic-related genes Bax, Bcl-2, Caspase-3, Caspase-6, and Caspase-7. The proliferation of HeLa cells was inhibited by overexpression of Tg LITAF. Apoptotic fluorescence assay further revealed that Tg LITAF participated in the apoptotic process of HeLa cells. Western blotting analysis showed that overexpression of Tg LITAF increased endogenous level of cleaved Caspase-7. Taken together, these results revealed that Tg LITAF participates in the innate immune response to the pathogen invasion in blood clams and induces apoptosis in HeLa cells. Highlights: We first cloned and identified the LITAF gene from the blood clam T. granosa. Tg LITAF was ubiquitously expressed in all tissues examined with the highest expression in the gills. Tg LITAF was activated significantly in vivo by V. alginolyticus and LPS stimulation. In vitro studies indicated that Tg LITAF promoted apoptosis of HeLa cells.